Small Lateral Meniscus Tears Propagate and are Detrimental to Knee Kinematics and Contact Forces. Issue 6 (28th June 2019) - Novaretti, Joao; Herbst, Elmar; Chan, Calvin; Debski, Richard; Musahl, Volker
Aims and Objectives: To quantify propagation of small vertical lateral meniscus tears located in the posterior horn during simulated cyclic cutting maneuvers on a robotic testing system and the resulting changes in knee kinematics and forces. Materials and Methods: 14 fresh-frozen human cadaveric knees (mean age: 74.8 ± 14.4) were mounted onto a 6-DOF robotic testing system. Knees with osteoarthritis greater than grade II were excluded. A small vertical tear in the posterior horn of the lateral meniscus medial to the popliteus tendon was created via a posterior arthrotomy. Tear length was measured with a custom-made device (accuracy 0.2 mm, inter-rater reliability 0.914). In 6 specimens, the ACL was resected arthroscopically, whereas in 8 knees the ACL was left intact. 10Nm valgus and 5Nm external rotation moment combined with 250N of axial compression were applied while the knees were continuously flexed from full extension to 90° of flexion for 500 cycles. Meniscus tear length was measured after each 100 cycles. After the measurements, the posterior capsule and skin were closed in a standardized fashion. Knee kinematics, the in situ force in the ACL, the resultant force in the lateral meniscus, and bony contact forces at the tibiofemoral joint were calculated at 30°, 60°, and 90° of knee flexion. A repeated measures ANOVA was used to compared the outcome parameters between knee states (p < 0.05). Results: In intact knees, small vertical lateral meniscus tears propagated significantly from baseline to 100, 200, 300, 400, and 500 cycles (all p < 0.001). This corresponds to a tear propagation of 28.7% ± 5.4%. Similarly, in ACL deficient knees meniscus tear propagation was significant throughout all sets of cycles (p = 0.001). This corresponds to a tear propagation of 26.1% ± 8.3%. While in intact knees, external tibial rotation was significantly increased by up to 45.5% after meniscus tear propagation, knee kinematics were not significantly affected in ACL deficient knees (NS). The resultant forces in the lateral meniscus increased with tear propagation in the intact knees by up to 54.1%. Likewise, the resultant forces in the lateral meniscus increased in the ACL deficient knees by up to 116.5% (p < 0.05). In intact knees, bony contact forces at the tibiofemoral joint increased with meniscus tear propagation by up to 91.9% (p < 0.05), which was comparable to ACL deficient knees. Conclusion: The data of this study suggest, that small vertical lateral meniscus tears propagate significantly regardless of the integrity of the ACL and after only 100 cycles of knee loading. The findings of the current robotic study are in contrast to recent clinical studies that found that small, vertical and stable tears in the posterior horn of the lateral meniscus could be left in situ. However, based on the current data, such tears do propagate over time regardless of the integrity of the ACL, which might alter knee kinematics and resultant forces in the lateral meniscus as well as bony contact forces at the tibiofemoral joint.